KEKERASAN KOGNITIF DAN HATE CRIME PADA ANAK USIA DINI DI TK/PAUD KOTA AMBON - Ainun Diana Lating (DIALEKTIKA, 2019)
ABSTRACT Cognitive development not only affects the child's understanding of the physical world, but the social world as well. Children at the age of 5 to 7 years is a golden age for the child. In fact many children at the age of 5 to 7 years in the city of Ambon now preoccupied by various kinds of tutoring. Cognitive violence in early childhood is a cognitive development in preoperational stage forced to think at a concrete operational stage. The condition of early child who attended school in kindergarten in Ambon city, as much as 33% (2,409 PD) followed private lesson, not only one, but two, three tutoring. Result of research that not all students who follow private lessons or classical tutoring do hate crime, as much as 11% (265 PD). Hate crime is a hate speech. Key word: cognitive violence; hate crime; early children